ON THE CONSTITUTIONAL AND LEGAL CHARACTER OF REPRESENTATIVE BODIES OF THE STATE IN A HISTORICAL CONTEXT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Institutions of representative democracy have become the subject of analysis in the constitutional and legal dimension. The study of political reality using the methodology has made it possible to identify the generalized properties of political systems, which is manifested in its organization in the process of forming representative democracy. The purpose of this article is to analyze established scientific ideas about the nature of democracy, the essence of the formation of representative bodies in the historical context in various political systems, which contributes to the conceptual refinement of the definitive content of general categories and the typology of representative institutions. As a practical value, it can be recognized that political processes show the absence of a single technology of political transformations, therefore, for each state, the issue of developing its own optimal model of transformations is actualized. The conducted analysis showed that the analysis of the nature of representative power has a long process of evolution and is practically identical to the models formed in the constitutional legislation of modern democratic states.
Keywords: representative bodies; state; democracy; constitutional and legal nature; management system; political system; constitution.